Comparing the Physician Assistant National Certifying Examination Pass Rate of Graduates From Programs Utilizing Distance Education to the National Average. Issue 2 (June 2021) - Forbes, Jennifer; Smith, Anntara; Papa, Jared; Sparrell, Marvin
Abstract : Purpose: The goal of this study was to compare the Physician Assistant National Certifying Examination (PANCE) pass rate of graduates from physician assistant (PA) programs utilizing distance education to the national average of PANCE pass rates. Methods: The Physician Assistant Education Association online PA program directory was used to obtain the name and number of physician assistant (PA) programs that offered distance education in their curriculum. The National Commission on Certification of Physician Assistants PANCE Exam Performance Summary Report was reviewed for each PA program that offered distance education. The 5-year first-time taker mean pass rate for all PA programs offering distance education was calculated and compared to the 5-year national first-time taker average for all PA programs in the United States over the same 5-year period. Results: The mean 5-year first-time taker pass rate for PA programs offering distance education was 96.9%. The 5-year national first-time taker average pass rate for all PA programs was 96.0%. Conclusion: The results of this study show that graduates from PA programs utilizing distance education are effectively prepared to pass the PANCE and do so at a rate that is higher than the national mean for all PA programs.